Use of Argon Plasma Coagulation and Endoscopic Hemoclips for Postsurgical Gastrointestinal Fistula - Abdullah Sohail; Ahmad Khan; Hamza Shah; Ragheb Rezko (Case Reports in Gastrointestinal Medicine)
A 72-year-old male was diagnosed with a duodenal mass and underwent extensive surgical resection. The patient’s post-op course was complicated by an anastomotic leak that was first treated conservatively; however, his condition continued to deteriorate. An upper endoscopy was performed, which showed misplacement of drain forming a fistulous track through the lumen of the bowel. We removed the drain and used argon plasma coagulation to de-epithelize the lumen and closed the fistula with hemostasis clips. The patient’s clinical status improved significantly. Our case emphasizes the success of endoscopic techniques as an alternative option in the management of postsurgical anastomotic leaks and fistulas in the right clinical setting and patient population.